The impact of parents' stress on parents' and young childrens' mental health—Short- and long-term effects of risk and resilience factors in families with children aged 0–3 in a representative sample - Löchner, Johanna; Ulrich, Susanne M.; Lux, Ulrike (Stress and Health, 2024)
Stress in parents has a significant impact on parenting and infant's development. However, few studies have examined cross-sectional and longitudinal links on risk and resilience of burdened families. Thus, this study aimed to investigate subjective risk and resilience factors on family well-being. Data stem from the 2015 nationwide study “Children in Germany” (“Kinder in Deutschland” – KiD 0–3). Parents of children aged zero to 3 years (N = 8.063) were recruited from random probability-sampled paediatric clinics (n = 271) across Germany. Risk and resilience variables such as parents' perceived stress (PSS-4), competence, isolation and attachment (PSI), as well as parental inner anger (items from CAP), relationship quality (DAS-4) and the child's negative emotionality (items from SGKS) were assessed at baseline in addition to demographic variables to predict parents' mental health (PHQ-4) and negative emotionality of the child at baseline (T1) and in the 2-year follow-up (T2) using linear regression models. At baseline, parents' mental health was predicted by inner anger, the child's negative emotionality and being a single parent (R2 = 45.1%) at baseline, but only by parenting competence at the two-year-follow-up (R2 = 25.1%). The child's negative emotionality was predicted (R2 = 27.5%) by the child's age, and parental inner anger and competence, attachment, perceived stress, mental health as well as education background. At two-year-follow-up, the child's age, single parenthood, social welfare benefit, child's negative emotionality at baseline, relationship quality and competence were significant predictor variables (R2 = 22.8%). This study highlights the impact of specific risk and resilience factors not only on parents' mental health but also the child's negative emotionality in the short and long-term in early childhood. Universal, but also selective prevention programs should increase parents' resilience (e.g., focusing on self-efficacy, competence, coping strategies).
CRIS-Team Scopus Importer:2024-11-26
Keywords: family well-being; infancy; longitudinal study; parental mental health; risk and resilience